1992
DOI: 10.1093/treephys/11.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Mild ozone exposure alters 14C dynamics in foliage of Pinus taeda L.

Abstract: To explore the physiological mechanisms underlying ozone-induced growth reductions in loblolly pine (Pinus taeda L.), seedlings were exposed to sub-ambient (charcoal-filtered), ambient or twice-ambient ozone in open-top chambers for three growing seasons. In the final year of exposure, current-year needle fascicles were labeled with (14)CO(2) and the incorporation of (14)C into biochemical fractions was followed for 48 hours. Irrespective of ozone treatment, losses of (14)C-assimilates from foliage to respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…In our previous studies, it was reported that net photosynthetic rate, starch grain size in chloroplasts and whole-plant dry mass of F. crenata seedlings were reduced by the exposure to O 3 (Yonekura et al 2001a, b). The exposure to O 3 caused the partition of assimilated carbon into organic acid rather than into starch (Friend and Tomlinson 1992). Therefore, the O 3 -induced reductions in the concentrations of carbohydrates and elements in the leaves of F. crenata seedlings are considered to be mainly due to the reduction of net photosynthesis and CO 2 fixation, and the inhibition in the amount of assimilated carbon partitioned into starch and protein.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, it was reported that net photosynthetic rate, starch grain size in chloroplasts and whole-plant dry mass of F. crenata seedlings were reduced by the exposure to O 3 (Yonekura et al 2001a, b). The exposure to O 3 caused the partition of assimilated carbon into organic acid rather than into starch (Friend and Tomlinson 1992). Therefore, the O 3 -induced reductions in the concentrations of carbohydrates and elements in the leaves of F. crenata seedlings are considered to be mainly due to the reduction of net photosynthesis and CO 2 fixation, and the inhibition in the amount of assimilated carbon partitioned into starch and protein.…”
Section: Discussionmentioning
confidence: 99%
“…1990 ; Amundson et al . 1991 ; Friend & Tomlinson 1992; Kainulainen et al . 1994 ) of conifers in growth chamber experiments after higher O 3 exposure concentrations than used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, accumulation of starch following exposure to O 3 has been reported ( Luethy‐Krause & Landolt 1990). Friend & Tomlinson (1992) concluded that O 3 ‐induced decrease in foliar starch concentration could be a result of decreased allocation of current photosynthate to starch or increased mobilization of starch pools. They also suggested that foliar starch could be a promising indicator of O 3 stress because it was sensitive to short‐term fluctuations in O 3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Since O 3 reduces carbon gain by limiting stomatal diffusion, lowering Rubisco activity, inducing early senescence and increasing carbon cost for tissue repair and antioxidant synthesis, it drastically decreases source strength and carbon availability for export to sink tissues. Additionally, increased soluble sugar content and carbohydrate retention have been observed in source tissue exposed to chronic O 3 concentration (from 0 to 110 ppb) (Friend and Tomlinson 1992;Grantz and Farrar 1999;Grantz and Yang 2000), suggesting a decrease in carbon export under O 3 . A lower leaf sucrose export and higher carbohydrate level would lead to feedback regulation of photosynthesis and therefore partly explain the reduction in carbon assimilation.…”
Section: O 3 -Induced Signalling In Treesmentioning
confidence: 98%